La motivación en el proceso de enseñanza aprendizaje de los alumnos del “Proyecto FAPT” - Endara Granda, Diana Carolina (2021)
The present investigation was oriented to solve the following research problem: How to strengthen motivation in people with unfinished schooling during the teaching-learning process?; considering as a general objective: Develop a set of workshops to strengthen motivation in people with unfinished schooling during the teaching-learning process in the Vicente León Educational Unit Project "FAPT -TODOS ABC", to achieve this, the quantitative approach aided by the survey as a diagnostic tool. The elaboration of the set of workshops for the strengthening of motivation in people with unfinished schooling during the teaching-learning process was feasible from the criteria of specialists and users and the results obtained in practice allowed to corroborate its effectiveness in solving the problem. While it is possible to improve, interest in learning, average academic performance, class attendance, completion of learning tasks and the state of satisfaction with teaching-learning aspects associated with intrinsic motivation.